Single molecule fluorescence studies of viral transcription - Periz Coloma, FJ (2014)
Rotaviruses are the single most common cause of fatal and severe childhood diarrhoeal illness worldwide (>125 million cases annually). Rotavirus shares structural and functional features with many viruses, such as the presence of segmented double-stranded RNA genomes selectively and tightly packed with a conserved number of transcription complexes in icosahedral capsids. Nascent transcripts exit the capsid through 12 channels, but it is unknown whether these channels specialise in specific transcripts or simply act as general exit conduits; a detailed description of this process is needed for understanding viral replication and genomic organisation. To test these opposing models, a novel single-molecule assay was developed for the capture and identification (CID) of newly synthesised specific RNA transcripts. CID combines the hybridisation of transcripts with biotinylated and FRET compatible labelled ssDNAs with the implementation of recent developments in single molecule fluorescence such as alternating laser excitation (ALEX) and total internal reflection fluorescence (TIRF) microscopy. CID identifies and quantifies specific transcripts of rotavirus based on a FRET/Stoichiometry (E*/S) value of the hybridised labelled probes. I used CID to pull down the capsid on the surface slide and identify partially extruded transcripts of three different segments 2, 6 and 11. The findings presented in this thesis support a model in which each channel specialises in extruding transcripts of a specific segment, that in turn is linked to a single transcription complex. The method can be extended to study other transcription systems including E.coli, and can be further developed as a potential diagnostic tool.